The SAGES Manual of Pediatric Minimally Invasive Surgery - Walsh, Danielle S.; Ponsky, Todd A.; Bruns, Nicholas E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This manual provides a comprehensive, state-of-the art review of this field, and will serve as a valuable resource for adult and pediatric surgeons at all stages of experience with interest in the use of minimally invasive surgical techniques in children. This book will review the pediatric surgical disorders that are currently treatable with these techniques. After a basic summary of the disorder, the preoperative evaluation and preparation is presented. Each chapter focuses on a detailed discussion of the surgical procedure, inclusive of anesthesia, positioning, instrumentation, and materials. Emphasis is placed on technique and tips for particularly challenging aspects of the operation. A description of the expected postoperative course and common complications of each procedure follows. The outcomes literature to include any advances since the original outcomes and expected future advances for the diagnosis and procedure is presented. It provides a concise yet comprehensive summary of the current status of the field that will help guide patient management and stimulate investigative efforts. All chapters are written by experts in their fields and include the most up to date scientific and clinical information.
Physiologic Considerations for Minimally Invasive Surgery in Infants and Children -- Pediatric Laparoscopic and Thoracoscopic Instrumentation -- Pediatric Endoscopic Instrumentation -- Minimally Invasive Approaches to the Pediatric Thyroid and Parathyroid -- Bronchoscopy and Tracheobronchial Disorders -- Thoracoscopic Thymectomy -- Thoracoscopic Ligation of the Patent Ductus Arteriosus -- Thoracoscopic Aortopexy -- Thoracoscopic Sympathectomy -- Thoracoscopic Approach to Eventration of the Diaphragm -- Minimally Invasive Approaches to Congential Diaphragmatic Hernias -- Thoracoscopic Repair of Esophageal Atresia and Tracheoesophageal Fistula -- Thoracoscopic Approaches to Congential Lung Lesions -- Thoracoscopic Lung Biopsies and Resections in Children -- Thoracoscopic Treatment of Pediatric Chylothorax -- Treatment of Empyema in Children -- Thoracoscopic Approach to Pediatric Mediastinal Masses -- Minimally Invasive Approaches to Esophageal Disorders: Strictures, Webs, and Duplications -- Esophageal Replacement Surgery in Children -- Minimally Invasive Approachese to Achalasia -- Minimally Invasive Approaches to GERD and Hernia in Children -- Laparoscopic Pyloromyotomy -- Minimally Invasive Gastrostomy -- Laparoscopic Duodenoduodenostomy -- Laparoscopic Approach to Intestinal Atresia -- Laparoscopic Resection of Abdominal Cysts and Duplications -- Anomalies of Intestinal Rotation: Laparoscopic Ladd's Procedure -- Laparoscopic Exploration for Pediatric Chronic Abdominal Pain -- Laparoscopic Lysis of Adhesions for Pediatric Bowel Obstruction -- Laparoscopic Meckel Diverticulectomy -- Laparoscopic Management of Pediatric IBD -- Laparoscopic Management of Intussusception -- Laparoscopic Appendectomy -- Laparoscopic Approach to Enteral Access for Chronic Constipation -- Laparoscopic-assisted Pull-through for Hirschsprung's Disease -- Laparoscopic-Assisted Anorectal Pull-Through for Anorectal Malformations -- Laparoscopic Pediatric Inguinal Hernia Repair -- Laparoscopic Epigastric Hernia Repair -- Minimally Invasive Approach to Pediatric Pancreatic Disorders -- Laparoscopic Cholecystectomy for Biliary Dyskinesia, Cholelithiasis and Cholecystitis -- Laparoscopic Treatment of Biliary Atresia -- Laparoscopic Treatment of Choledochal Cysts -- Laparoscopic Splenectomy -- Laparoscopic Adrenalectomy in Children -- Minimally Invasive Support for Placement of Ventricular Shunts -- Bariatric Surgery in Adolescents -- Laparoscopic Management of Pediatric Ovarian Disease -- Laparoscopic Management of Testicular Disorders (Cryptorchidism and Varicocele) -- Laparoscopic Resection of Renal Masses -- Minimally Invasive Management of Urinary Reflux -- Laparoscopic Approaches to Peritoneal Dialysis.
Keywords: Medicine; Surgery; Minimally invasive surgery; Pediatric surgery; Medicine & Public Health; General Surgery; Pediatric surgery; Minimally invasive surgery